2022
DOI: 10.1159/000524477
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Thyroid Dysregulation, and Thyroid Cancer in Children and Adolescents: Proposed Impending Mechanisms

Abstract: Stress is a potential catalyst for thyroid dysregulation through cross-communication of the hypothalamic-pituitary-adrenal and hypothalamic-pituitary-thyroid (HPT) axes. Stress and stressors exposure motivates molecular mechanisms affecting compound feedback loops of the HPT axis. Whilst, there is evidence of connection between stress and thyroid dysregulation, the question whether this connection is implicated in the development of thyroid cancer (TC) remains unanswered. In view of the rising incidence of TC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…Just as with GH supplementation, deficiencies of iodine are treated with iodine supplementation ( 29 ). Recent research into developmental thyroid disorders include uncovering potential mechanisms by which stress alters the hypothalamic-pituitary-thyroid (HPT) axis as a source of inflammation that leads to thyroid cancer ( 30 ).…”
Section: Hormones Before Pubertymentioning
confidence: 99%
“…Just as with GH supplementation, deficiencies of iodine are treated with iodine supplementation ( 29 ). Recent research into developmental thyroid disorders include uncovering potential mechanisms by which stress alters the hypothalamic-pituitary-thyroid (HPT) axis as a source of inflammation that leads to thyroid cancer ( 30 ).…”
Section: Hormones Before Pubertymentioning
confidence: 99%
“…However, both groups should pay more attention to their thyroid health if they have a family history of diabetes or hypertension, sleep too much or have an abnormal body mass index (BMI) [33], and increase the frequency of medical check-ups. The incidence of thyroid cancer is also due to the accumulation of bad habits over time, and many studies have shown an association between stress and the development of thyroid cancer [36], [37], [38]. Therefore, it is important to maintain a happy mood and an optimistic and positive attitude towards life and good lifestyle habits.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Thyroid system has also been largely involved in the immune dysregulation observed during chronic stressful conditions (Cremaschi et al, 2000). In addition, prolonged thyroid dysregulation during stress has been suggested to be linked to child and adolescent thyroid cancers, in particular through their effects on the immune system (Kyriacou et al, 2023). The mechanisms linking thyroid and immune functions are well-identified.…”
Section: Infl Ammationmentioning
confidence: 99%